The Gambia : Second Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses The Gambia's Second Review Under the Staff-Monitored Program (SMP). The program is broadly on track. All quantitative targets for end-December 2017 and end-March 2018 were met as were most of the structural benchmarks, with three of them needing to be re-phased and redefined. However, the continuous target on contracting new nonconcessional external debt was breached, owing to a USD 25 million loan. The IMF staff supports the completion of the second review under the SMP. The IMF staff also encourages the authorities to ensure macroeconomic stability and step up the pace of structural reforms to strengthen economic governance and tackle the legacy of debilitating public debt to pave the way for a possible Extended Credit Facility arrangement.